Adding fish oil and natural antioxidants to whey protein improves eccentric-exercise recovery in soccer players - Philpott, J. D.; Donnelly, C.; Walshe, I. H.; Dick, J.; Mckinlay, E.; Galloway, S. D.; Tipton, K. D.; Witard, O. C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The physical demands of soccer match-play is known to involve changing speed and direction, repeated sprints and explosives jumps, that predominantly requires eccentric type muscle contractions. Such movements often result in the phenomenon termed muscle damage. Protein feeding has been shown to preserve the functional capacity of skeletal muscle after eccentric exercise. Since fish oil derived n-3 polyunsaturated fatty acids (n-3PUFA) exhibit anti-inflammatory properties, combining ingestion of fish oil with protein may facilitate recovery. Therefore, the primary aim of the present study was to assess the influence of 6 wk supplementation with a juicebased antioxidant-rich drink containing a combination of n-3PUFA, whey protein and vitamin D on muscle function and soreness, inflammation and soccer performance during exercise recovery. Methods: Competitive soccer players (n=27) were assigned to one of three conditions. Drink-A contained n-3PUFA (550 mg DHA, 550 mg EPA), whey protein (15 g) and vitamin D (3 µg). Drink-B contained whey protein (15 g) and vitamin D (3.9 µg) and Drink-C was an isocaloric carbohydrate control. Eccentric exercise consisted of 12 sets of unilateral knee extension/flexion contractions on both legs separately. Statistical analyses included conventional p-value and magnitudebased inferential approaches. Results: Eccentric exercise impaired maximal force and increased ratings of muscle soreness (p<0.05). Post supplementation, blood %n-3PUFA/total PUFA was greater in Drink-A (36 ± 6) vs. Drink-B (24 ± 3, p<0.05) or Drink-C (23 ± 2, p<0.05). Maximum force loss during recovery tended (p = 0.10) to be less in Drink-A (-19 ± 22%) vs. Drink-C (-30 ± 10%). Muscle soreness (dominant leg), expressed as AUC during 72 h exercise recovery, tended to be less in Drink-A (791 ± 549 mm x 72 h) vs. Drink-B (1403 ± 779 mm x 72 h, p=0.08) and Drink-C (1298 ± 621 mm x 72 h p=0.10). The blood concentration of c-reactive protein tended (p=0.09) to be lower in Drink-A (AUC: 42 ± 11 mg/L x 72 h) vs. Drink-C (AUC: 83 ± 42 mg/L x 72 h, p < 0.05). Drink-A elicited a very likely (79-96%) beneficial effect on agility t-test performance vs. Drink-B and Drink-C. Discussion: A juice-based antioxidant-rich drink, containing n-3PUFA, whey protein and vitamin D, appears to mediate a reduced feeling of muscle soreness after eccentric exercise and translates into improved muscle function and soccer-specific performance during acute recovery. Hence, the benefit of whey protein ingestion to exercise recovery may be enhanced by the addition of n-3PUFA and natural antioxidants in competitive soccer players.